Analisis Kekosongan Jabatan Guna Mengoptimalkan Kinerja Karyawan Perumda Bank Gresik - M Alifudin Al Islami; Moh Agung Surianto (CERED Indonesia Institute, 2022)
In a company, the level of success can be seen by several factors, one of which is the performance of employees who are able to make the company successful. However, if the employee's performance is disrupted such as a vacancy in a company, it will not be optimal in the success of the company. The problem that occurs in Perumda Bank Gresik is that there is a vacancy that makes the company's performance not run well. The research setting in this study is Perumda Bank Gresik which is a company owned by the Gresik Regency government which is engaged in financial institutions (Banking). Jl. Basuki Rahmat No.18, Bedilan, Kebungson, Kec. Gresik, Gresik Regency, East Java 61114 / (031) 3988875. The research method used by the author in compiling this final project is descriptive method. The results of this study are important to fill vacancies in a company, especially Perumda Bank Gresik, because this will affect the performance of employees and companies that make the company successful or not in achieving its vision and mission.